Design Thinking applied to User Experience Design - Vargas Márquez, Bragean Luis (2021)
Today we are immersed in technology and the way in which we communicate with this is the user interface, to enable the interaction between the user and an artifact, system or machine, so large companies use Design Thinking techniques and Design of user interfaces, to get closer to customers empathically, so that they can know their real needs and be really interested in the details of their lives. Generating empathy with our customers means putting their problems, more than our solutions, first. The problem that is sought to be solved in the user experience design part, is that the designer does not know if the user will find the proposed interface friendly, that is why Design Thinking is one of the most used methods in order to put yourself in the position of the end user. In this article we intend to show how Design Thinking can be applied to the generation of UX user experiences. Each of the phases involved in the generation of the user experience is also explained: Research, Organization, Prototyping, Testing and Design.